(untitled) (Dhaka University Journal of Biological Sciences, 2023)
Relapse is a highly burdensome phenomenon in mental health care as it creates distress not only in the individual but also in the family and society. Therefore, detecting factors that are potential to develop relapse and the management measures for a psychiatric patient after relapse are very much important. The study was carried out to know whether different types of psychiatric patients were experiencing relapse due to the outbreak of the COVID-19 pandemic. A survey with telephonic interviews was conducted with 55 mental health professionals of Bangladesh. A total of 250 psychiatric patients’ information was collected. It was found that 56.40% of them relapsed after outbreak of the COVID-19 and most of them were females and young adult patients. Patients reported of suffering from anxiety disorders, depressive disorders, and obsessive-compulsive disorders before the COVID-19 relapsed more than the other disorders. The most reported causes of their relapse were fear of having COVID-19, feeling frightened and anxious due to uncertainty in the COVID-19 situation, feeling depressed due to social isolation and adjustment problems, and conflicts with family members. Relapsed patients had taken services mostly through telemedicine and tele-counseling rather than face-to-face services. Recommendations to the management of relapse of psychiatric patients in a pandemic based on the results of the study are discussed. Dhaka Univ. J. Biol. Sci. 32(2): 149-157, 2023 (July)